The perfect hope - Roberts, Nora. frey50 (New York : Berkley Books, 2012)
The Montgomery brothers have been the talk of Boonsboro, ever since they decided to renovate the old Inn into an intimate and handsome new Bed and Breakfast. Beckett and Owen have both found love in the process, but what of Ryder, the third Montgomery brother?
Keywords: Brothers; Bed and breakfast accommodations; Man-woman relationships; Boonsboro (Md.); Love stories